Synthesis and Reactivity of Some Peroxo Complexes of Zirconium(IV) Thorium(IV) and Uranium(VI) Ions Containing a Quadridentate, Quadrinegative Ligand and a Pentadentate Dinegative Schiff Base: Peroxo Complexes of Zr, Th and U (Biological Sciences - PJSIR, 2010)
Some new peroxo complexes of zirconium, thorium and uranium containing a quadridentate, quadrinegative organic ligand and a pentadentate dinegative Schiff base ligand have been synthesized and characterized by elemental analyses, magnetic measurements and various spectral studies. Oxygen transfer reactions of some complexes toward different substrates have been investigated. The Schiff base, LH2, was derived from the condensation of 2,6-diaminopyridine with salicylaldehyde. The present ligands undergo deprotonation during complexation coordinating with (OOOO)4-  and –ONNNO–  donor sequences, respectively. The complexes have the compositions, [M(O ) (OOOO)]. 2H O+  [M = Zr(IV) 2 3 and Th(IV), OOOO = DCTA], [UO(O2) (OOOO)].2H3O ; [M(O2) (ONNNO)] [M = Zr(IV) and Th(IV),  ONNNO  =  L] and [U(O) (O2) (ONNNO)].H2O. The chelate effect of the quadridentate and pentadentate ligands stabilizes the metal peroxide moieties precluding oxygen transfers to organic and inorganic substrates. The mode of coordination is also influenced by the ?-donor electronic nature of the multidentate ligands. The IR spectral data also indicate that the ?1(O-O) stretching modes decrease with and increase in the atomic number of the metals in a group.Some new peroxo complexes of zirconium, thorium and uranium containing a quadridentate, quadrinegative organic ligand and a pentadentate dinegative Schiff base ligand have been synthesized and characterized by elemental analyses, magnetic measurements and various spectral studies. Oxygen transfer reactions of some complexes toward different substrates have been investigated. The Schiff base, LH2, was derived from the condensation of 2,6-diaminopyridine with salicylaldehyde. The present ligands undergo deprotonation during complexation coordinating with (OOOO)4-  and –ONNNO–  donor sequences, respectively. The complexes have the compositions, [M(O ) (OOOO)]. 2H O+  [M = Zr(IV) 2 3 and Th(IV), OOOO = DCTA], [UO(O2) (OOOO)].2H3O ; [M(O2) (ONNNO)] [M = Zr(IV) and Th(IV),  ONNNO  =  L] and [U(O) (O2) (ONNNO)].H2O. The chelate effect of the quadridentate and pentadentate ligands stabilizes the metal peroxide moieties precluding oxygen transfers to organic and inorganic substrates. The mode of coordination is also influenced by the ?-donor electronic nature of the multidentate ligands. The IR spectral data also indicate that the ?1(O-O) stretching modes decrease with and increase in the atomic number of the metals in a group.